The Routledge handbook of Jews and Judaism in late antiquity - Hezser, Catherine (Routledge Handbooks, 2024)
This volume focuses on the major issues and debates in the study of Jews and Judaism in late antiquity (3rd to 7th c. C.E.), providing cutting-edge surveys of the state of scholarship, main topics and research questions, methodological approaches, and avenues for future research. Based on both Jewish and non-Jewish, literary and material sources, this volume takes an interdisciplinary approach involving historians of ancient Judaism, scholars of rabbinic literature, archaeologists, epigraphers, art historians, and Byzantinists. Developments within Jewish society and culture are viewed within the respective regional, political, cultural, and socio-economic contexts in which they took place. Special focus is given to the impact of the Christianization of the Roman Empire on Jews, from administrative, legal, social, and cultural points of view. The contributors examine how the confrontation with Christianity changed Jewish practices, perceptions and organizational structures, such as, for example, the emergence of local Jewish communities around synagogues as central religious spaces. Special chapters are devoted to the eastern and western Jewish Diaspora in Late Antiquity, especially Sasanian Persia but also Roman Italy, Egypt, Syria and Arabia, North Africa, and Asia Minor, to provide a comprehensive assessment of the situation and life experiences of Jews and Judaism during this period. The Routledge Handbook of Jews and Judaism in Late Antiquity is a critical and methodologically sophisticated survey of current scholarship aimed primarily at students and scholars of Jewish Studies, Study of Religions, Patristics, Classics, Roman and Byzantine Studies, Iranology, History of Art and Archaeology. It is a valuable resource for anyone interested in Judaism and Jewish history--